Atypical Presenting Symptoms of Acute Onset Systemic Lupus Erythematosus with Enteritis and Cystitis - Yagita, Mayu (Case Rep Med, 2016)
Lupus enteritis and lupus cystitis are relatively rare manifestations of systemic lupus erythematosus. Some patients develop severe complications such as bowel perforation, infarction, obstruction, or irreversible bladder dysfunction. Early diagnosis is critical for management of lupus enteritis and cystitis. We report a 48-year-old Japanese man who presented with initial manifestations of abdominal pain, severe diarrhea, and bloody feces. The diagnosis was delayed due to atypical initial symptoms, resulting in clinical worsening. Physicians should be aware of typical computed tomography findings of lupus enteritis and lupus cystitis.